Performance analysis of reverse electrodialysis stacks: Channel geometry and flow rate optimization. (1st September 2018) - Long, Rui; Li, Baode; Liu, Zhichun; Liu, Wei
Abstract: In this paper, the optimal channel geometry and flow rate of the concentrated and diluted solutions under the maximum net power output for the reverse electrodialysis (RED) stacks at a confined size are systematically investigated. A model considering the change in volume flow rate along the flow direction is employed to illustrate the process of the RED stack. For systematisms, under the maximum net power output, we first consider the optimal channel thicknesses at a given identical inlet flow rate and then the optimal channel thicknesses and flow rates. The profiles of flow rate, concentration, power density, and hydrodynamic loss along the flow direction are discussed. The net power output and energy efficiency for different membranes under the above two optimization situations are analyzed and compared. The results reveal that the optimal channel thickness of the high-concentration (HC) compartment is slightly larger than that of the low-concentration (LC) compartment for a given identical inlet flow rate. When both channel thickness and flow rate are optimized, the optimal channel thicknesses and volume flow rates of the HC compartment are, respectively, less than those of the LC compartment and the net power output and energy efficiency are significantly improved. Highlights: Impacts of channel geometry and flow rate on RED maximum net power output at confined size are investigated. Maximum net power output and energy efficiency under different optimization spaces are systematically discussed. Certain coupling of channel geometry and flow rate leads to significant performance improvement.